Ultrasound in rheumatology. (March 2018) - Freeston, Jane; Vital, Ed
Abstract: Ultrasound has become an essential tool for rheumatologists to diagnose and treat musculoskeletal disorders. It can image bone erosions and osteophytes, tendons, entheses, synovium and cartilaginous structures in multiple joints in a cheap, convenient examination within the clinic; it can also assist in interventions such as joint and tendon sheath injection. This has altered clinical practice in several contexts. Evaluation of subclinical synovitis is valuable to define the extent of inflammatory disease. In early arthritis clinics, inflammatory changes and bone erosion can be used to identify patients who need early aggressive immunosuppressive therapy. In established inflammatory arthritis, the presence of inflammatory changes during clinical remission predicts longer term outcomes and may allow stratification of therapy changes. Ultrasound has also elucidated pathological processes, for example in the structures involved in dactylitis or the subtypes of lupus arthritis. In specific complex joints, such as the shoulder, ultrasound allows a dynamic evaluation of multiple structures and a more precise diagnosis of pathology than clinical examination alone or other imaging techniques. In this article, we review the structures and pathologies that are well imaged by ultrasound, and its principal applications in the rheumatology clinic.